2006
DOI: 10.1007/s11099-005-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses and proline content of mature and young leaves of sunflower plants under water deficit

Abstract: In mature and young leaves of sunflower (Helianthus annuus L. cv. Catissol-01) plants grown in the greenhouse, photosynthetic rate, stomatal conductance, and transpiration rate declined during water stress independently of leaf age and recovered after 24-h rehydration. The intercellular CO 2 concentration, chlorophyll (Chl) content, and photochemical activity were not affected by water stress. However, non-photochemical quenching increased in mature stressed leaves. Rehydration recovered the levels of non-phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 22 publications
(19 reference statements)
5
37
0
1
Order By: Relevance
“…The accumulation of osmolyte compounds such as proline in the cells as a result of water stress is often associated with a possible mechanism to tolerate the harmful effect of water shortage (CLIFFORD et al, 1998). In sunflower, the young stressed leaves synthesized nearly seven times more proline than non-stressed leaves while the mature stressed leaves synthetized it only four times more (CECHIN et al, 2006). This may explain the lower leaf young stressed leaves found in this study.…”
Section: Resultsmentioning
confidence: 48%
“…The accumulation of osmolyte compounds such as proline in the cells as a result of water stress is often associated with a possible mechanism to tolerate the harmful effect of water shortage (CLIFFORD et al, 1998). In sunflower, the young stressed leaves synthesized nearly seven times more proline than non-stressed leaves while the mature stressed leaves synthetized it only four times more (CECHIN et al, 2006). This may explain the lower leaf young stressed leaves found in this study.…”
Section: Resultsmentioning
confidence: 48%
“…The highest proline was observed under high stress conditions (25AW) in RGS003 (142.63 nmol/g fresh weight), and the lowest proline was observed in the RGS003 cultivar under normal conditions (23.68 nmol/g fresh weight) (Figure 3). Cechin et al (2006) investigated the response of photosynthesis and proline under stress in leaves of the safflower oil plant and showed that drought stress increased proline accumulation in young leaves. Din et al (2011) found that metabolic factors such as free proline content in leaves increased significantly under severe drought stress at both the reproductive and the productive stage.…”
Section: Prolinementioning
confidence: 99%
“…After four days of stress imposition, leaf and shoot dry weight and RWC were reduced about 23%, 22% and 13%, respectively but stem dry weight accumulation was not affected (Table 1). The observed reduction in leaves dry weight is a result of high sensitivity of young leaves to changes in water supply (Cechin et al, 2006) since cell division and elongation are influenced by leaf water status or cell turgor (Heckenberger et al, 1998). Applications of SNP in wheat seedlings has been found to confer water deficit tolerance by maintaining more water than the well watered plants (García-Mata & Lamattina, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Proline works as both an osmoprotectant and as a redox-buffering agent possessing antioxidant property under conditions of stress (KaviKishor & Sreenivasulu, 2014). Accumulation of proline under drought stress was found in several plants, particularly in young leaves (Cechin et al, 2006). Furthermore, foliar applied proline ameliorated the adverse effects of water stress on growth and photosynthetic capacity of two maize cultivars (Ali et al, 2007).…”
Section: Introductionmentioning
confidence: 99%